Infant feeding practices in three Latin American countries in three decades: what demographic, health, and economic factors are relevant? - Meira, Camila Abadia Rodrigues; Buccini, Gabriela; Azeredo, Catarina Machado; Conde, Wolney Lisbôa; Rinaldi, Ana Elisa Madalena (Frontiers in Nutrition, 2023)
Introduction: Studies in Latin America have focused either on analyzing factors associated with exclusive breastfeeding (EBF) or infant formula (IF). Purpose: Analyze the association between economic, sociodemographic, and health factors with EBF, mixed milk feeding (MixMF), and exclusive use of IF in three Latin American and Caribbean countries in the 1990s, 2000s, and 2010s. Methods: Cross-sectional time-series study using data from Demographic and Health Surveys between the 1990s and 2010s in Colombia (1995 to 2010), Haiti (1994 to 2017), and Peru (1996 to 2012) accounting for a sample of 12,775 infants under 6 months. Hierarchical logistic multilevel regression models were used to estimate the adjusted association between infant feeding outcomes (EBF, MixMF, exclusive use of IF) and contextual level DHS survey decade (1990s, 2000s and 2010s) and economic factors (Gross Domestic Product by purchasing power parity, female wage and salaried workers, labor force participation rate female) as well as individual level sociodemographic (maternal age, maternal education, number of children in the household, wealth index, mother living with a partner, area of residence, mother working outside of home), and health factors (breastfed in the first hour, C-section). Results: Factors associated with EBF cessation were c-section (OR:0.76;95%CI:0.64,0.92), mothers working outside of the home (OR:0.79;95%CI:0.69,0.90), families in the highest income quintile (OR:0.64;95%CI:0.49,0.84), and female wage and salaried workers (OR:0.92;95%CI:0.91,0.94). MixMF was associated with women with higher education (OR:1.54;95%CI:1.21,1.97), mother working outside of the home (OR:1.26;95%CI:1.10,1.43), c-section (OR:1.37; 95%CI:1.15,1.62), families in the highest income quintiles (OR:2.77;2.10,3.65). and female wage and salaried workers (OR:1.08;95%CI:1.05,1.09). Exclusive use of IF was associated with a mother working outside of the home (OR: 2.09;95%CI:1.41,3.08), c-section (OR:1.65;95%CI:1.09,2.51), families in the highest income quintiles (OR:12.08;95%CI:4.26,34.28), the 2010s (OR: 3.81;95%CI:1.86,7.79), and female wage and salaried workers (OR1.12;95%CI:1.07,1.16). Discussion/Conclusion: Factors related to women empowerment and gender equality jeopardized EBF and favored the exclusive use of IF in Latin America. Therefore, workplace interventions to promote, protect, and support breastfeeding practices are key to reducing exclusive use of IF.